Brokers of Bias in the Criminal Justice System: Do Prosecutors Compound or Attenuate Racial Disparities Introduced by Police? - Harrington, Emma; Shaffer, Hannah (The Review of Economics and Statistics, 2025)
In criminal cases, prosecutors have the discretion to adjust arresting officers’ charges and so can offset racial disparities introduced by police. Yet prior research suggests that prosecutors instead compound earlier disparities. We investigate prosecutors’ impacts on disparities using sentencing discontinuities in North Carolina, where defendants with slightly longer criminal histories face mandatory prison. Prosecutors can sidestep these mandatory-prison laws by reducing qualifying defendants’ charges. Between 1995 and 2019, Black defendants were initially less likely — but ultimately became more likely — to benefit from charge reductions that avoid mandatory prison. This reversal is driven by arrests typically initiated by police.